(untitled) (Research, Society and Development, 2021)
The aim of this study was to extract the starch from the Tommy Atkins mango (Mangifera Indica) and to evaluate the effect on the chemical and physico-chemical characteristics of tilapia pâtés. Starch was extracted and total starch, protein, moisture, ash, acidity, gelling, swelling and solubility, water and oil absorption capacity, and microbiological (thermotolerant coliforms, Escherichia coli, molds and yeasts, and Staphylococcus aureus) analyzes were performed. Pâtés were formulated with mango starch and corn starch, and the pH, lipids, moisture, ash, microbiological (Thermotolerant coliforms, Escherichia Coli, Salmonella sp., Staphylococcus aureus), instrumental color, sensory and stability characteristics were analyzed during storage. The extracted material presented 72.69% total starch, 2.96% protein, gelation in concentrations of 8 to 14%, greater swelling power and solubility at 95 °C, water retention capacity of 58 g/100 g and 45 g/100g of oil. The application of mango starch in pâté did not change its physical-chemical characteristics in comparison with pâté using corn starch. There were low counts of total coliforms, molds and yeasts in the starch and an absence of Salmonella, Escherichia Coli, Staphylococcus Aureus in the starch and pâtés in the microbiological analyzes. It was found that the pâté samples were stable for 30 days of cold storage, with low color and microbiological changes. The pâtés obtained good acceptance in the sensory evaluation with scores between 7 and 8. This study showed that the application of mango starch in tilapia pâté formulations is feasible, thereby constituting a means of reusing this residue.